Bottom trawl surveys in the northern Bering Sea indicate recent shifts in the distribution of marine species - Stevenson, Duane E.; Lauth, Robert R. (Polar biology, 2019)
The climate regime in the eastern Bering Sea has recently been dominated by a pattern of multi-year stanzas, in which several successive years of minimal sea-ice formation and warm summer temperatures (e.g., 2002–2005, 2014–2017) alternate with several years of relatively extensive sea-ice formation and cold summer temperatures (e.g., 2006–2013). This emerging climate pattern may be forcing long-term changes in the spatial distributions of the Bering Sea’s marine fauna. The National Marine Fisheries Service’s Alaska Fisheries Science Center recently conducted two bottom trawl surveys covering the entire Bering Sea shelf from the Alaska Peninsula to the Bering Strait. The first, in the summer of 2010, was conducted during a cold year when the majority of the continental shelf was covered by a pool of cold (< 2 °C) water. The second, in the summer of 2017, was during a warmer year with water temperatures above the long-term survey mean. These two surveys recorded significantly different spatial distributions for populations of several commercially important fish species, including walleye pollock ( Gadus chalcogrammus ), Pacific cod ( Gadus macrocephalus ), and several flatfish species, as well as jellyfishes. Population shifts included latitudinal displacement as well as variable recruitment success. The large-scale distributional shifts reported here for high-biomass species raise questions about long-term ecosystem impacts, and highlight the need for continued monitoring. They also raise questions about our management strategies for these and other species in Alaska’s large marine ecosystems.